2013
DOI: 10.1016/j.physa.2013.01.029
|View full text |Cite
|
Sign up to set email alerts
|

Phase diagram of mechanically stretched DNA: The salt effect

Abstract: The cations, in form of salt, present in the solution containing DNA play a crucial role in the opening of two strands of DNA. We use a simple non linear model and investigate the role of these cations on the mechanical unzipping of DNA. The Hamiltonian is modified to incoporate the solvent effect and the cations present in the solution. We calculate the melting temperature as well as the critical force that is required to unzip the DNA molecule as a function of salt concentration of the solution. The phase di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 57 publications
1
25
0
Order By: Relevance
“…4B, shows a good match with the experimental phase diagram obtained by Huguet et al [19]. The earlier result [11] that showed some mismatch at the lower concentrations is showing better match by including the sequence dependent salt concentration. To get more insight of the sequence dependent salt effect on the force induced transition in DNA, we take different segments of λ-phage DNA [36] that is having different GC content.…”
Section: Forced Induced Transitionsupporting
confidence: 85%
See 2 more Smart Citations
“…4B, shows a good match with the experimental phase diagram obtained by Huguet et al [19]. The earlier result [11] that showed some mismatch at the lower concentrations is showing better match by including the sequence dependent salt concentration. To get more insight of the sequence dependent salt effect on the force induced transition in DNA, we take different segments of λ-phage DNA [36] that is having different GC content.…”
Section: Forced Induced Transitionsupporting
confidence: 85%
“…An additional term in the Morse potential is the solvent term which simulates the formation of hydrogen bonds with the solvent, once the hydrogen bonds are stretched by more than their equilibrium values. The "tanh"term in the potential enhances the energy of the equilibrium configuration and the height of the barrier below which the base pair is closed [11,30,31].…”
Section: The Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The counterion theory proposed by Manning explains the stability of the DNA molecule due to the presence of salt in the solution [3,4]. The stretching and unzipping behaviour of the DNA molecule in the presence of cations have also been discussed by several groups [5,19,20]. These results show that the mechanical stability of the DNA molecule also increases with the concentration of cations.…”
Section: Introductionmentioning
confidence: 96%
“…For the current investigations we adopt the standard Peyrard Bishop Dauxois (PBD) model [26,27] and modify the potentials appearing in the model. In our earlier work, we showed that the PBD model has enough detail to explain the thermal as well as mechanical stability of DNA molecules at lower strengths of salt and with varying salt concentration [5,28]. Our presentation in the current manuscript is organized as follows.…”
Section: Introductionmentioning
confidence: 99%